Context, Types, and Consequences of Violence Across the Life Course: A Qualitative Study of the Lived Experiences of Transgender Women Living With HIV - Lacombe-Duncan, Ashley (Journal of interpersonal violence, 2022)
Violence is a known driver of HIV vulnerability among transgender (trans) women, who are disproportionately impacted by HIV globally. Violence is also a barrier to accessing HIV prevention, treatment, and support. Yet, little is known about the everyday experiences of violence faced by trans women living with HIV, who live at the intersection of a marginalized gender identity and physical health condition. To address this gap, this study draws on semi-structured, individual interviews conducted 2017–2018 with a purposive sample (selected based on diverse identities) of trans women living with HIV (n = 11) participating in a large, community-based cohort study in three Canadian provinces. Framework analysis was used to identify key themes, patterns within themes between participants, and patterns across themes among participants. Findings showed that trans women living with HIV experience specific contexts of violence shaped at the intersection of stigma based on gender identity, gender expression, and HIV status, among other identities/experiences. Violence experienced in childhood (e.g., familial rejection, bullying) increased trans women’s likelihood of being exposed to a violent social context in young adulthood (e.g., state violence perpetuated by the police, interpersonal violence perpetuated by sexual partners, and community violence perpetuated by society-at-large/the general public), which increased trans women’s HIV vulnerability; once living with HIV trans women were subjected to discursive violence from healthcare providers. These multiple forms of violence have serious consequences for trans women living with HIV’s ongoing social, mental, and physical well-being. The findings suggest that interventions are urgently needed to reduce violence against trans women in childhood and young adulthood, in addition to reducing violence against trans women living with HIV perpetuated by healthcare providers in adulthood, to both proactively and responsively promote their safety, health, and well-being.